Analisis Literasi Keberlanjutan Awal Siswa SMA pada Materi Pencemaran Lingkungan Terintegrasi Sdgs Poin 6 - Indriyani Amalia; Sariwulan Diana; Riandi Riandi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Sustainability literacy is an important urgency today, this is related to the knowledge and understanding of individuals in making decisions and taking further action on sustainability as an effort to prepare for life in the future. This study aims to analyze the level of initial sustainability literacy of high school students on environmental pollution material integrated with SDGs point 6 regarding the availability of clean water and sustainable sanitation. The research method used is quantitative descriptive with instruments in the form of sustainability literacy essay questions that refer to three main aspects of sustainability literacy, namely knowledge, skills, and mindset. The study was conducted at a high school in Garut Regency in May 2025 with a sample of 70 grade X students selected through purposive sampling techniques. The results showed that most students (60%) were in the very low category in sustainability literacy, especially in the knowledge aspect. This indicates the need for more transformative and contextual learning interventions to increase students' understanding and concern for sustainability issues. This study recommends the integration of the SDGs concept explicitly in the biology learning process in schools.